2022
DOI: 10.3389/fmicb.2022.965132
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the impact of manure on the environmental antibiotic residues and resistance pool

Abstract: Frontiers in Microbiology 02 frontiersin.org seems to reduce or eliminate most of antibiotics residues, enteric bacteria, ARB and different representative ARG in manure more rapidly and effectively than lagoon storage. Our review highlights that despite the body of research accumulated in the last years, there are still important knowledge gaps regarding the contribution of manure to the AMR emergence, accumulation, spread and risk of human exposure in countries with high clinical resistance rates. Land microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 159 publications
0
6
0
Order By: Relevance
“…It has the added benefit of degrading antibiotics present in manure, thereby reducing their concentration and potentially decreasing the proliferation of antibiotic-resistant bacteria. 178 In addition to this, it significantly diminish the presence of antimicrobial-resistance gene in manure, by up to 90%. The higher temperatures involved in anaerobic digestion can further enhance its effectiveness in reducing antibiotic-resistant bacteria, making thermophilic anaerobic digestion more efficient in this regard compared to mesophilic anaerobic digestion.…”
Section: Preventive Measures Of Spread Of Antimicrobial Resistance Fr...mentioning
confidence: 98%
“…It has the added benefit of degrading antibiotics present in manure, thereby reducing their concentration and potentially decreasing the proliferation of antibiotic-resistant bacteria. 178 In addition to this, it significantly diminish the presence of antimicrobial-resistance gene in manure, by up to 90%. The higher temperatures involved in anaerobic digestion can further enhance its effectiveness in reducing antibiotic-resistant bacteria, making thermophilic anaerobic digestion more efficient in this regard compared to mesophilic anaerobic digestion.…”
Section: Preventive Measures Of Spread Of Antimicrobial Resistance Fr...mentioning
confidence: 98%
“…Additionally, toxicological assessments in soil environments have indicated that tetracyclines and certain transformation products could pose moderate to high ecological risks to terrestrial organisms. Furthermore, substantial amounts of drug residues resulting from direct or indirect contamination can be detected in animal manure, which is commonly utilized as fertilizer in agriculture [ 17 ]. These residues can build up in crop tissues, and eventually find their way into the food chains that feed animals and humans [ 17 ].…”
Section: Sources Of Drug Residues In Farm Animalsmentioning
confidence: 99%
“…To mitigate the dissemination of ARGs, manure is often preprocessed before being applied to land. Recent reviews have shown that aerobic thermophilic and postdigestion composting could reduce >80% of ARGs, but different antibiotics may persist in the liquid (e.g., sulfonamides) or solid (e.g., tetracycline) phases of the manures and even after anaerobic digestion and composting [ 126 ]. Efforts should be made to address these concerns and develop strategies to ensure the safe and responsible use of organic fertilizers in agriculture.…”
Section: Agronomic Practices Phytomicrobiomes and Plant Diseasesmentioning
confidence: 99%